Thymocyte selection-associated high mobility group box gene (TOX) is aberrantly over-expressed in mycosis fungoides and correlates with poor prognosis - Huang, Yuanshen (Impact Journals LLC, 2014)
Mycosis fungoides (MF) often mimics the common chronic inflammatory skin diseases and is difficult to be diagnosed with certainty, partly because of the lack of well-characterized molecular markers. Previously, we discovered that TOX, a key T cell development regulator,was aberrantly over-expressed in early stage MF. In the current multi-center study involving two independent patient cohorts, we determined the prevalence of TOX over-expression in the full spectrum of MF skin biopsies, and tested if TOX expression levels correlated with long term clinical outcomes. We examined TOX expression levels in 113 MF biopsies. We found that the MF biopsies expressed higher TOX mRNA than the controls in both cohorts (17.9 fold in cohort 1, P = 0.002; 5.8 fold in cohort 2, P < 0.0001). In addition, thicker skin lesions such as plaques and tumors expressed even higher TOX levels than thinner patches. Further, TOX over-expression differentiated MF from the controls (area under the curve [AUC]=0.87, P < 0.0001). Finally, high TOX mRNA levels correlated with increased risks of disease progression (P = 0.003) and disease-specific mortality (P = 0.008). In conclusion, TOX may be a useful marker for improving MF diagnosis and prognostication.